2010
DOI: 10.1002/hfm.20234
|View full text |Cite
|
Sign up to set email alerts
|

Designing and evaluating a crew resource management training for manufacturing industries

Abstract: This article presents the evaluation of crew resource management (CRM) training specifically designed for employees within manufacturing industries. The central objective of this training program was to improve teamwork, communication, and stress management skills as well as to increase the workers' situational awareness of potential errors that can occur during the manufacturing process. Eighty employees, all of whom were working in a production unit for gearbox manufacturing, participated in the training pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…SA supervisor observer ratings and SA self‐assessments were assessed once prior and twice after CRM training. Based on this method triangulation, the results revealed a significant increase of SA and correlations among these measures (Marquardt et al, ). It was found that SA scores, measured with high reliability, significantly increased after a CRM intervention (including SA‐training for error prevention), which refers to sufficient sensitivity to SA changes.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…SA supervisor observer ratings and SA self‐assessments were assessed once prior and twice after CRM training. Based on this method triangulation, the results revealed a significant increase of SA and correlations among these measures (Marquardt et al, ). It was found that SA scores, measured with high reliability, significantly increased after a CRM intervention (including SA‐training for error prevention), which refers to sufficient sensitivity to SA changes.…”
Section: Introductionmentioning
confidence: 99%
“…While the concept of SA has been applied most frequently to the field of aviation and medicine, it has rarely been discussed in relation to manufacturing tasks (Marquardt, Robelski, & Jenkins, ). Even though the triple‐loop learning model of human error and SA should be applicable to any other industry, there are some reasons why the empirical testing was assigned to manufacturing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations